The Mesoscopic Damage Mechanism of Jointed Sandstone Subjected to the Action of Dry–Wet Alternating Cycles - Liang Zhang; Guilin Wang; Runqiu Wang; Bolong Liu; Ke Wang (Applied Sciences, 2024)
The effect of the dry–wet cycle, characterized by periodic water level changes in the Three Gorges Reservoir, will severely degrade the bearing performance of rock formations. In order to explore the effect of the dry–wet cycle on the mesoscopic damage mechanism of jointed sandstone, a list of meso-experiments was carried out on sandstone subjected to dry–wet cycles. The pore structure, throat features and mesoscopic damage evolution of jointed sandstone with the action of the dry–wet cycle were analyzed using a-low-field nuclear magnetic resonance (NMR) technique. Subsequently, the impact on the mineral content of dry–wet cycles was studied by small angle X-ray scattering (SAXS). Based on this, the mesoscopic damage mechanism of sandstone subjected to dry–wet cycles was revealed. The results show that the effects of the drying–wetting cycle can promote the development of porous channels within sandstone, resulting in cumulative damage. Besides, with an increase in dry–wet cycles, the proportion of small pores and pore throats decreased, while the proportion of medium and large pores and pore throats increased. The combined effects of extrusion crush, tensile fracture, chemical reaction and dissolution of minerals inside the jointed sandstone contributed to the development of mesoscopic pores, resulting in the increase of porosity and permeability of rock samples under the dry–wet cycles. The results provide an important reference value for the stability evaluation of rock mass engineering under long-term dry–wet alternation.